1968
DOI: 10.4141/cjps68-082
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SOIL pH ON THE PHYTOTOXICITY OF SIMAZINE TO STRAWBERRIES

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1970
1970
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Adsorption of the s-triazines by soil colloids is dependent on the pH of the system, and many studies (4,5,8,9,10) have shown less phytotoxicity of the s-triazine under acid condi tions. This increased adsorption of various s-triazines by clay or organic matter has been considered the result of protonation of the basic molecule (1,2,3,7,10).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of the s-triazines by soil colloids is dependent on the pH of the system, and many studies (4,5,8,9,10) have shown less phytotoxicity of the s-triazine under acid condi tions. This increased adsorption of various s-triazines by clay or organic matter has been considered the result of protonation of the basic molecule (1,2,3,7,10).…”
Section: Introductionmentioning
confidence: 99%
“…3); thus the margin of crop tolerance would be greater in soils with a lower pH. Further work is necessary to determine how carrot growers should be advised to use metribuzin with respect to soil pH, as in the case of simazine use in strawberry in Atlantic Canada (Leefe 1968).…”
Section: Field Experiments Crop Tolerancementioning
confidence: 99%
“…The effect of pH on herbicidal activity, either in conjunction with liming or not, has received some attention in recent years. Thus in Canada, simazine injured strawberries more after liming (Leefe, 1968), and Nearpass (1965) found deeper penetration and reduced decomposition of simazine in limed than unlimed soil.…”
Section: Introductionmentioning
confidence: 94%